Faith of St. Paul : transformative gift of divine power - Harrisville, Roy A. III. (Eugene, Oregon Pickwick Publications, 2019)
For generations, scholars who study the letters of St. Paul have argued about "being-in-Christ" and "justification by faith" as though they were competing theologies. They have argued about faith as divine gift or human work, and more recently the faith of Jesus Christ has been called into question. Harrisville proposes a provocative and simple solution to these issues by examining scholarly assumptions and presenting the faith of St. Paul as a dynamic and life-changing power.Participation in Christ and righteousness by faith are actually complimentary expressions for the same concept. The apostle's faith was not self-engendered but a gift that transformed him into a believer. Taking a more organic approach to understanding the faith of St. Paul, this book provides a path toward reconciling entrenched positions and providing a fresh perspective by presenting the apostle's concept of faith as a transformative gift of divine power.
Includes bibliographical references (pages 107-110) and indexes.
Keywords: Paul, -- the Apostle, Saint -- Theology; Paul, -- the Apostle, Saint; Faith -- Religious aspects -- Christianity; Justification (Christian theology); Faith -- Religious aspects -- Christianity; Justification (Christian theology); Theology